2015
DOI: 10.1590/0100-69912015003012
|View full text |Cite
|
Sign up to set email alerts
|

A porcine model for teaching surgical cricothyridootomy

Abstract: ABSTRACT ABSTRACT ABSTRACTObjective: Objective: Objective: Objective: Objective: To evaluate the acceptability of an educational project using A porcine model of airway for teaching surgical cricothyroidotomy to medical students and medical residents at a university hospital in southern Brazil. MethodsMethods Methods Methods Methods: we developed a teaching project using a porcine model for training in surgical cricothyroidotomy. Medical students and residents received lectures about this surgical technique an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…9 A prior study has shown that practicing on animal models allows physicians to become familiar with cricothyroidotomy. 10 From our experience and reports from the United States, we found that exposure to tracheotomy for otorhinolaryngology residents has been declining, and residents perform fewer tracheostomies each year. 11 Due to concerns for inadequate training of young residents, we developed an animal model-based tracheotomy course.…”
Section: Introductionmentioning
confidence: 85%
“…9 A prior study has shown that practicing on animal models allows physicians to become familiar with cricothyroidotomy. 10 From our experience and reports from the United States, we found that exposure to tracheotomy for otorhinolaryngology residents has been declining, and residents perform fewer tracheostomies each year. 11 Due to concerns for inadequate training of young residents, we developed an animal model-based tracheotomy course.…”
Section: Introductionmentioning
confidence: 85%
“…There are a variety of cricothyrotomy simulators available for clinicians to practice on, including cadaver-based models, porcine models, live-animal models, and manufactured simulators. Cricothyrotomy training on porcine models has been documented and accepted as a training model for learning this infrequently performed procedure [13]. However, many of these models do not include a critical obstacle in doing a successful cricothyrotomy: intraoperative bleeding [14].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical ex vivo pig model used in this research was developed and tested by Spencer et al 20 in UNIOESTE. From this reference, we managed to improve its structure, including it as the main element to test the constructive methodology proposed on this work.…”
Section: Chest Drainage Teaching and Training For Medical Students Umentioning
confidence: 99%